2011
DOI: 10.1002/app.33789
|View full text |Cite
|
Sign up to set email alerts
|

Terpolymers from lactide and bisphenol a derivatives: Scale‐up, properties, and blends

Abstract: Terpolymerization of L-lactide (LA) and bisphenol A derivatives was performed on few hundred gram scale, and the resultant terpolymer (TP) was characterized by gel permeation chromatography, infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), and thermogravimetric analysis. Moderate molecular weight (M n $ 12 kg/ mol) TP was achieved with glass transition temperatures about 100 C (DSC and DMA). The TP exhibited improved thermal stability compared with polyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Based on image analysis of a TEM image (Figure ), the average length and thickness of NCC over 150 particles were 171 ± 79.7 and 15.1 ± 5 nm, respectively. These dimensions are in accordance with the literature …”
Section: Results and Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Based on image analysis of a TEM image (Figure ), the average length and thickness of NCC over 150 particles were 171 ± 79.7 and 15.1 ± 5 nm, respectively. These dimensions are in accordance with the literature …”
Section: Results and Discussionsupporting
confidence: 92%
“…There is no consensus in the literature about the surface energy data of polymer materials (even using the same technique such as contact angle measurements). For instance, one study reported 10.5, 29.7, and 40.2 mJ/m 2 for the polar part, dispersion part, and total surface energy of PLA . Another study reported the following values for PLA: 39.6 mJ/m 2 for dispersion, 3.9 mJ/m 2 for polar, and 43.5 mJ/m 2 for total surface energy .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, interface energy of original CB and PLA was calculated as 13.2 mN/m, and interface energy of PLA- g -KH560/CB and PLA was calculated as 1.5 mN/m (Table ). These results mean that interface energy PLA composites membrane could be reduced by modification of CB particle. …”
Section: Results and Discussionmentioning
confidence: 80%